Symmetry reduction and some exact solutions of a nonlinear five-dimensional wave equation - Fedorchuk, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
By using decomposable subgroups of the generalized Poincaré group P(1,4), we perform a symmetry reduction of a nonlinear five-dimensional wave equation to differential equations with a smaller number of independent variables. On the basis of solutions of the reduced equations, we construct some classes of exact solutions of the equation under consideration.